Implementasi Sistem Monitoring Jaringan Menggunakan Protokol Snmp Dengan Metode Prototyping Di Telkom Majene - Nurani Rani; Melyani; Muhammad Furqan Ramadani (STMIK KHARISMA Makassar, 2026)
The need for a network monitoring system capable of detecting disruptions quickly and accurately is increasingly pressing with the rapid development of information technology. Currently, the existing disruption detection process is still performed manually, which is quite time-consuming, ranging from 2 to 3 hours, hampering handling and reducing service quality. This research aims to implement a network monitoring system using the Simple Network Management Protocol (SNMP) based on a dashboard and Telegram notifications to improve detection time efficiency. The research method used was prototyping, encompassing the stages of requirements analysis, design, implementation, and testing. System functionality was evaluated using Black Box Testing. The results showed that the implementation of this system significantly accelerated disruption detection time, from an average of 2.5 hours to 1.75 hours, a 30% increase in efficiency. Although Black Box testing showed an 80% success rate with some caveats regarding input validation, overall, this system has proven effective in improving disruption detection speed and supporting technician performance in optimal network infrastructure management.